OPERATING CONDITION RECOGNITION DEVICE AND TRANSMISSION CONTROLLER OF AUTOMATIC TRANSMISSION UTILIZING IT - TOMIZAWA NAOMI (1990)
PURPOSE:To provide the most suitable control by analyzing factors according to the operating condition parameters such as throttle valve opening, engine speed, and recognizing and judging the operating conditions such as running at jamming traffic and in an urban district, high-speed running, sport running, etc. CONSTITUTION:The operating amount of plural operating condition parameters including at least throttle valve opening, engine speed is sampled per unit time by a detecting means A. At this time, a typical data preparation means B evaluates series data and allocates them into large and small divisions through an allocation means, and prepare typical data according to its frequency and distribution Then a satisfaction calculation means C makes an evaluation and allocation for the calculation of satisfaction based on the evaluation function by plural operating condition parameters pre-determined, and an operating condition judgement means D judges the operating conditions such as running at jammed traffic and in an urban district, high-speed running, sport running, etc., from the satisfaction of these plural evaluation functions, and makes response to the operating conditions and transmission patterns for control. It is thus possible to provide the most suitable control.